Kasus Pelecehan Seksual di Telegram: Ditinjau Dari Teori Spiral of Silence - J, Mutia Sahira; Aulia, Rahmadhani (LITERAKOM: Jurnal Literasi dan Komunikasi, 2023)
The use of digital technology today is much easier than the last 10 years, especially with the Industrial Revolution 4.0. However, this progress is not balanced with education and a sense of responsibility in its use. As a result, there are rampant cases of sexual harassment and violence in the digital space. One of them is a case of sexual harassment that occurred on telegram. The purpose of the study was to see how the public response and audience reaction in responding to sexual harassment on Telegram social media and see how important the Twitter application for victims of sexual harassment to speak up for the incident that has happened to them. The research method used in this study is a literature research method and is qualitative. The theory used is the Spiral of Silence Theory. The results showed that many women victims of sexual harassment occurred on telegram, but because they were afraid to speak out, most victims just kept silent and chose to keep themselves silent and were afraid to report their cases. Departing from that, a lot of attention and opinions were thrown by the public on one of the social media, namely Twitter which raised the issue of sexual harassment on Telegram which made the Spiral of silence theory really exist in media.